2004
DOI: 10.1146/annurev.psych.55.090902.142028
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception

Abstract: This chapter focuses on one of the first steps in comprehending spoken language: How do listeners extract the most fundamental linguistic elements-consonants and vowels, or the distinctive features which compose them-from the acoustic signal? We begin by describing three major theoretical perspectives on the perception of speech. Then we review several lines of research that are relevant to distinguishing these perspectives. The research topics surveyed include categorical perception, phonetic context effects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
260
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(284 citation statements)
references
References 128 publications
17
260
1
6
Order By: Relevance
“…By contrast, several competing theories have suggested that a purely sensory analysis is sufficient for speech classification [24]. The discovery of mirror neurons [7] has provided the direct neural demonstration that the motor system becomes activated during perception.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, several competing theories have suggested that a purely sensory analysis is sufficient for speech classification [24]. The discovery of mirror neurons [7] has provided the direct neural demonstration that the motor system becomes activated during perception.…”
Section: Discussionmentioning
confidence: 99%
“…One line of research that could bear on this issue would consist of experiments using non-speech stimuli, which has been used to bear on the articulation/acoustic debate in other domains of phonetic theories-especially on the debate about the objects of speech perception (see Diehl et al 2004 for a review). One such non-speech experiment on sound symbolism was conducted by O'Boyle and Tarte (1980), who did not find a significant correlation between frequencies of pure tones and the figures that they represent.…”
Section: Summary: Articulatory or Acoustic?mentioning
confidence: 99%
“…Especially in the sub-second range, accurate duration encoding is instrumental for many complex behaviors such as precise motor control (i.e. in activities such as sport and dance), speech recognition and generation, and the processing of social cues (Ambadar, Cohn, & Reed, 2009;Buhusi & Meck, 2005;Diehl, Lotto, & Holt, 2004;Janata & Grafton, 2003;Mauk & Buonomano, 2004;Merchant & Georgopoulos, 2006;Schmidt, Ambadar, & Cohn, 2005). Recently, there has been a renewed interest in studying this temporal aspect of our behavior and the way in which our brain encodes this information.…”
Section: Introductionmentioning
confidence: 99%